Regulatory Mechanism of lncRNAs in M1/M2 Macrophages Polarization in the Diseases of Different Etiology - Jiang, Ping; Li, Xiaopeng (Frontiers in Immunology, 2022)
Precise expression and regulation of genes in the immune system are important factors for organisms to produce strong immunity to pathogens and limit autoimmunity. In recent years, an increasing number of studies have shown that long noncoding RNAs (lncRNAs) are closely related to immune function and can participate in the regulation of immune responses by regulating immune cell differentiation, development, and function. As immune cells, the polarization response of macrophages (Mφs) plays an important role in immune function and inflammation. More and more studies have shown that c can regulate the phenotypic polarization of Mφs to M1 or M2 through a variety of mechanisms, promote Mφs to produce pro-inflammatory or anti-inflammatory effects, and participate in the pathogenesis of cancers, inflammatory diseases, infections, metabolic diseases and autoimmune diseases. In addition, it is of great significance to explore the regulatory mechanisms of lncRNAs on dynamic transition between different Mφs phenotypes. Thus, regulatory role of lncRNAs in the polarization of Mφs and its mechanism are discussed in this review.